2004
DOI: 10.1527/tjsai.19.73
|View full text |Cite
|
Sign up to set email alerts
|

A Sense Retrieving Method from a Noun for the Commonsense Feeling Judgment System

Abstract: keywords: commonsense judgment, sense, unknown word processing, concept base, degree of association SummaryWhen we humans receive uncertain information, we interpret it properly, so we can expand the conversation, and take proper actions. This is possible because we have "commonsense" concerning the word, which is built up from knowledge that is stored through long time experience. Among the commonsense we use in our every day lives it is thought that there are the commonsense concerning; quantity such as size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…When categorizing objective words and verb and normal and nominal adjective words, the ambiguity is judged from the relationships between words (Figure 4). To effectively use this knowledge database where a small amount of knowledge is registered to judge processing and emotions, I developed a proprietary "concept base" that automatically interprets limited knowledge broadly to respond to diverse expressions [6][7][8][9] (Figure 5). One result showed that this proposed method is capable of reproducing 74.2% of the emotion judgment ability.…”
Section: Estimation Of Emotions From Languagementioning
confidence: 99%
“…When categorizing objective words and verb and normal and nominal adjective words, the ambiguity is judged from the relationships between words (Figure 4). To effectively use this knowledge database where a small amount of knowledge is registered to judge processing and emotions, I developed a proprietary "concept base" that automatically interprets limited knowledge broadly to respond to diverse expressions [6][7][8][9] (Figure 5). One result showed that this proposed method is capable of reproducing 74.2% of the emotion judgment ability.…”
Section: Estimation Of Emotions From Languagementioning
confidence: 99%